Rapid assessment of forest canopy and light regime using smartphone hemispherical photography. Issue 24 (1st November 2017) - Bianchi, Simone; Cahalan, Christine; Hale, Sophie; Gibbons, James Michael
Abstract: Hemispherical photography (HP), implemented with cameras equipped with "fisheye" lenses, is a widely used method for describing forest canopies and light regimes. A promising technological advance is the availability of low‐cost fisheye lenses for smartphone cameras. However, smartphone camera sensors cannot record a full hemisphere. We investigate whether smartphone HP is a cheaper and faster but still adequate operational alternative to traditional cameras for describing forest canopies and light regimes. We collected hemispherical pictures with both smartphone and traditional cameras in 223 forest sample points, across different overstory species and canopy densities. The smartphone image acquisition followed a faster and simpler protocol than that for the traditional camera. We automatically thresholded all images. We processed the traditional camera images for Canopy Openness (CO) and Site Factor estimation. For smartphone images, we took two pictures with different orientations per point and used two processing protocols: (i) we estimated and averaged total canopy gap from the two single pictures, and (ii) merging the two pictures together, we formed images closer to full hemispheres and estimated from them CO and Site Factors. We compared the same parameters obtained from different cameras and estimated generalized linear mixed models (GLMMs) between them. Total canopy gap estimated from the first processing protocol for smartphone pictures was on average significantly higher than CO estimated from traditional camera images, although with a consistent bias. Canopy Openness and Site Factors estimated from merged smartphone pictures of the second processing protocol were on average significantly higher than those from traditional cameras images, although with relatively little absolute differences and scatter. Smartphone HP is an acceptable alternative to HP using traditional cameras, providing similar results with a faster and cheaper methodology. Smartphone outputs can be directly used as they are for ecological studies, or converted with specific models for a better comparison to traditional cameras. Abstract : Hemispherical photography (HP) is a common ground‐based method for forest canopy and light regime studies. Here we tested protocols for data acquisition and processing of hemispherical pictures obtained with smartphone cameras. Our results demonstrate that they are an acceptable alternative to traditional cameras, providing similar results with a faster and cheaper methodology. Through the methods that we propose, any forest practitioner could carry out advanced HP studies with the aid of a smartphone and a small and cheap fisheye lens.